Ethical Challenge of Fashion Influencers Endorsement: Analysing Communication and Consumption Culture - Moch Zihad Islami; Yoga Aditya Leite; Dian Aris Munandar; Yuana Novita Sari; Sonjoruri Budiani Trisakti (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2024)
The fast fashion trend is gaining popularity due to the presence of fashion influencers on social media despite its adverse impact on environmental sustainability. This research aims to explore the fashion influencers communication strategy, assess how fashion influencers endorsements contribute to the formation of consumptive culture, and investigate fashion influencers endorsement concepts that are more ethical. The qualitative research is used by employing the observations on six Indonesian fashion influencers Instagram accounts, and the interviews with three informants confirmed as being with three informants confirmed as affected by fashion influencers endorsement. The data were analysed using media content analysis and thematic analysis. The study concluded with three main findings. Firstly, fashion influencers employs persuasive and interactive communication strategies. Secondly, the formation of a consumptive culture results from the fashion expertise of influencers, which nurtures consumer satisfaction by promoting a consumptive lifestyle among consumers, even though they ultimately assess their consumption. Lastly, fashion influencers can be aligned to reconstruct more ethical endorsement by applying responsibility, sanctity, and sustainability principles.Tren fast fashion saat ini semakin populer karena kehadiran fashion influencer di media sosial meskipun memiki dampak buruk terhadap keberlanjutan lingkungan. Penelitian ini bertujuan untuk mengeksplorasi strategi komunikasi fashion influencer, menemukan pola konstruksi konten promosi fashion influencer terhadap budaya konsumtif, serta memberikan kerangka endorsement oleh fashion influencer yang lebih etis. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data berupa observasi terhadap enam orang fashion influencer Indonesia serta wawancara terhadap tiga orang yang terkonfirmasi telah terdampak oleh konten promosi fashion influencer. Data yang ada kemudian dianalisis menggunakan konten analisis media dan analisis tematik. Hasil penelitian menghasilkan tiga temuan utama. Pertama, strategi komunikasi fashion influencer yakni persuasif dan interaktif. Kedua, terbentuknya budaya konsumtif berawal dari keahlian fashion influencer yang kemudian menimbulkan kepuasan konsumen dengan mempromosikan gaya hidup konsumtif, meskipun pada akhirnya konsumen mengevaluasi pola konsumsinya. Terakhir, fashion influencer dapat diarahkan untuk merekonstruksi pendekatan endorsement-nya agar lebih etis, dengan menerapkan prinsip tanggung jawab, sakral, dan keberlanjutan.